Identification of miRNAs linked to peanut nodule functional processes - Figueredo, María Soledad (2020)
microRNAs (miRNAs) are non-coding small RNAs that regulate gene expression at post-transcriptional level. Thousands of miRNAs have been identified in legumes, but studies about miRNAs linked to peanut nodule functionality are scarce. In this work we analyzed transcriptional changes in peanut nodules to identify miRNAs involved in functional processes of these organs. We found 32 miRNAs precursors differentially expressed in nodules compared with roots, and predicted the potential targets of their corresponding mature miRNAs. Among them, 20 belong to 14 conserved miRNAs families and 12 are Arachis hypogaea-specific miRNAs. Expression levels of 3 miRNAs (ahy-miR399, ahy-miR159 and ahy-miR3508) were confirmed experimentally by qPCR. We also demonstrated that the expression of these miRNAs was not affected by inoculation of a biocontrol bacterium or a fungal pathogen. The catalogue of differentially expressed miRNA precursors and the expression of the corresponding mature miRNA potential targets in the nodules of A. hypogaea obtained in this work is a database of strong candidates, including A. hypogaea-specific miRNAs, for the regulation of the nodule functionality. The analysis of their role in this process will certainly lead to the characterization of essential regulators in these particular aeschynomenoid nodules.